STUDI TENTANG HYGIENE DAN SANITASI PADA USAHA SALON KECANTIKAN DI KOTA PAYAKUMBUH - Nasari, Wiza; Yusuf, Liswarti; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The research wasmotivated bythe problemsata beauty salonintownthatstillhas not noticedPayakumbuhaspectsrelated to surveillanceeffortson the healthof other individuals andthe environment. The purposeof this studyistoanalyzethe application ofhygieneandsanitationin thebeauty salon businessassociatethat isclassifiedin thecityPayakumbuh.Â Â Thisresearchmethodisdescriptivequantitative. Thestudypopulationwasallbeauty salonsinas many as21 piecesPayakumbuhsalon. The samples wereclassifiedassociatebeautysalonin the city, amounting to 8 Payakumbuhbeauty salonswithbeauty salonpersonnelnumbered45 people. Instruments used inthis research is aquestionnaire(questionnaire). The results obtained from the data that the individual employee hygiene in the beauty salon business Payakumbuh on maintaining the cleanliness of the body with both categories (82%), while maintaining the cleanliness of clothes with unfavorable category (63%). Sanitation in the beauty salon business Payakumbuh indicator requirements are 2 salons buildings that meet the requirements of building eight. On the cleanliness of the water quality indicators there are 4 salons that meet eight requirements of cleanliness of the water quality. On indicators of waste management, there are 3 salons that meet the four requirements of waste management. Onwastecontrolindicatorthere is not anysalonthat meetseightwastemanagement requirements. Onhygiene indicatorsaretoolsandmaterialsthat meeteight2salonhygienerequirements oftools and materials. Â Kata Kunci : Hygiene, Sanitasi, Usaha salon kecantikan.